Closed-cell carbon foams from diphenolic acid-based polybenzoxazine. (December 2015) - Zúñiga Ruiz, Camilo Javier; Szczurek, Andrzej; Martínez de Yuso Arisa, Alicia; Ronda, Juan Carlos; Cádiz, Virginia; Fierro, Vanessa; Celzard, Alain
Abstract: Highly porous polybenzoxazine-based vitreous carbon foams prepared by a self-blowing process followed by pyrolysis at 900 °C are presented. Both organic and carbon foams were described in terms of porosity and thermal and mechanical properties, but the investigations mainly focused on carbon foams, with additional Raman, mercury porosimetry and SEM studies. It is clearly shown that the special foaming process, unlike others previously reported for preparing the same kind of materials, allowed obtaining a significant fraction of closed cells. This feature, although rather common for many organic foams, is unique for carbon foams who had to endure significant release of volatile matters and shrinkage during pyrolysis. As a consequence, the lowest thermal conductivities ever reported for cellular vitreous carbon foams were measured.